Smbat Sparapet's chronicle - Smbat, Sparapet, 1208-1276. ([Dandenong South, Victoria] [Dandenong South, Victoria])
2 cilt (1. cilt xvii, 329 sayfa ; 2. cilt xv, 200 sayfa)
Keywords: “This set contains both volumes of Smbat Sparapet's Chronicle. This work is one of the gems of medieval Armenian literature and is an important part of Sophene’s Dual Language Series. In this series, we aim to make the most important works of ancient Armenian literature accessible to the broadest possible audience by placing the original Armenian text on the left-hand side and the corresponding English translation on the right-hand side. Smbat Sparapet’s Chronicle is a major source for the history of the Armenian Kingdom of Cilicia. Roughly three-quarters of the work consists of a summary of Matthew of Edessa’s Chronicle which describes the period from 951 to 1136 and its continuation by Gregory the Priest, covering the period from 1136-1162. Given that Matthew’s work has survived, by far the most important part of Smbat Sparapet’s Chronicle is its original contribution, devoted to the period from 1163 to 1272. As a statesman and general, Smbat Sparapet (“the Constable”) was a major participant in Cilician civil, military, and diplomatic affairs of the second half of the 13th century. An educated and literate individual, Smbat translated the Assizes of Antioch from French into Armenian, and probably also had some familiarity with Greek, Arabic, Turkish and Persian. He visited the Mongol court in Karakorum in 1248 and recorded some of his observations in a short letter in French to his brother-in-law Henry I of Cyprus. Such an individual certainly was uniquely well-informed to write a chronicle of his times“ --